2011
DOI: 10.18409/jas.v2i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Properties of semi-elementary imsets as sums of elemen- tary imsets

Abstract: We study properties of semi-elementary imsets and elementary imsets introduced by Studený [10]. The rules of the semi-graphoid axiom (decomposition, weak union and contraction) for conditional independence statements can be translated into a simple identity among three semi-elementary imsets. By recursively applying the identity, any semi-elementary imset can be written as a sum of elementary imsets, which we call a representation of the semi-elementary imset. A semi-elementary imset has many representations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…We denote this face by F A,B | C . In Kashimura et al 7 we have shown some remarkable facts on F A,B | C . Here we establish more basic facts on F A,B | C .…”
Section: Structure Of Faces Of Semi-elementary Imsetsmentioning
confidence: 66%
See 3 more Smart Citations
“…We denote this face by F A,B | C . In Kashimura et al 7 we have shown some remarkable facts on F A,B | C . Here we establish more basic facts on F A,B | C .…”
Section: Structure Of Faces Of Semi-elementary Imsetsmentioning
confidence: 66%
“…Our final result of this section concerns a product of skeletal functions for disjoint sets. These functions played an important role in Kashimura et al 7 Proposition 4.3. Let AB = N , A ∩ B = ∅ and consider f of the form…”
Section: Results On Extreme Rays Of the Supermodular Conementioning
confidence: 97%
See 2 more Smart Citations